Human ultrarare genetic disorders of sulfur metabolism demonstrate redundancies in H2S homeostasis - Kožich, Viktor; Schwahn, Bernd C; Sokolová, Jitka; Křížková, Michaela; Ditroi, Tamas; Krijt, Jakub; Khalil, Youssef; Křížek, Tomáš; Vaculíková-Fantlová, Tereza; Stibůrková, Blanka; Mills, Philippa; Clayton, Peter; et al. (Redox biology, 2022)
Regulation of H2S homeostasis in humans is poorly understood. Therefore, we assessed the importance of individual enzymes in synthesis and catabolism of H2S by studying patients with respective genetic defects. We analyzed sulfur compounds (including bioavailable sulfide) in 37 untreated or insufficiently treated patients with seven ultrarare enzyme deficiencies and compared them to 63 controls. Surprisingly, we observed that patients with severe deficiency in cystathionine β-synthase (CBS) or cystathionine γ-lyase (CSE) - the enzymes primarily responsible for H2S synthesis - exhibited increased and normal levels of bioavailable sulfide, respectively. However, an approximately 21-fold increase of urinary homolanthionine in CBS deficiency strongly suggests that lacking CBS activity is compensated for by an increase in CSE-dependent H2S synthesis from accumulating homocysteine, which suggests a control of H2S homeostasis in vivo. In deficiency of sulfide:quinone oxidoreductase - the first enzyme in mitochondrial H2S oxidation - we found normal H2S concentrations in a symptomatic patient and his asymptomatic sibling, and elevated levels in an asymptomatic sibling, challenging the requirement for this enzyme in catabolizing H2S under physiological conditions. Patients with ethylmalonic encephalopathy and sulfite oxidase/molybdenum cofactor deficiencies exhibited massive accumulation of thiosulfate and sulfite with formation of large amounts of S-sulfocysteine and S-sulfohomocysteine, increased renal losses of sulfur compounds and concomitant strong reduction in plasma total cysteine. Our results demonstrate the value of a comprehensive assessment of sulfur compounds in severe disorders of homocysteine/cysteine metabolism and provide evidence for redundancy and compensatory mechanisms in the maintenance of H2S homeostasis.
Keywords: Cysteine; sulfidy; Persulfide dioxygenase; Sulfur; Molybdenum cofactor; Cystathionine β-synthase; homocystein; síra; Sulfite oxidase; Hydrogen Sulfide; sulfan; Sulfides; cystein; Homocysteine; Humans; homeostáza; Cystathionine γ-lyase; Homeostasis; Sulfide:quinone oxidoreductase; lidé